Analysis of Indonesian population mortality based on life table for estimating net premiums for term life insurance - Amelia Putri; Dinie Triana; Sandi Dwi Payana (Lembaga Riset Mutiara Akbar, 2026)
Accurate determination of life insurance premiums requires mortality data that is representative of the characteristics of the insured population. This study aims to analyze the mortality patterns of the Indonesian population based on ASDR data from the SP2020 of the Central Statistics Agency, and apply it in estimating net premiums for term life insurance. The methods used include converting ASDR to probability of death (qx), reconstructing a 5-year abridged life table for productive ages 25–60 years, calculating the actuarial present value (APV) of death benefits, life annuity due, and net premiums based on the actuarial equivalence principle. The discount rate used is 5% with a sum insured of Rp100,000,000 and a policy term of 10 years. The results show that the qx value is relatively constant at 0.00264 in the age range of 25–46 years, then increases significantly to 0.02610 at age 60. The annual net premium for ages 25–46 years is recorded as stable at Rp251,428.57 and increases sharply to Rp467,838.75 at age 49. This study contributes to providing the first publicly accessible proxy life table from the 2020 Population Census aggregate data as an alternative to the Indonesian Mortality Table (TMI).